Applications of Fractional Calculus: Processing Signals - Dorian Valentin RADUCAN; Mihai REBENCIUC (Communications of International Proceedings, 2021)
Fractional calculation is a theory of arbitrary or even complex intervals and derivatives and is a generalization of the classic calculation and therefore preserves many of the basic properties. In this work we will present the importance of fractional calculation in a common domain in everyday life; we will present the processing signals and a specific method of speech signals such as the LPC method - Linear predictive coding (LPC) is a widely used technique in audio signal processing, especially in speech signal processing. We will also try to implement this method in a smart house/building with sensor help, and we will implement it using well-known programming languages. In order to achieve results that prove its usefulness, we will produce a series of simulations, from which we will draw conclusions why LPC method is the one of the best solution for signals processing.
Keywords: Fractional Calculus; Processing Signals; LPC Method